Impact of Informal Groups on Organisational Performance (International Journal of Scientific Research and Management (IJSRM), 2018)
The purpose of this study is to investigate the impact of informal groups on organizational performance. Informal groups are a very powerful social network which are constructed in response to and through actions of their members, informal groupings when viewed on the degree of their being informal, creates a managerial burden informally for managers who require additional competences to manage their activities. Informal groups exist to achieve group interest which may not necessarily be in tandem with the overall goals of the organization. The aim of this study is to identify why employees engage in informal groups. A survey research design was adopted and copies of questionnaire were administered on 319 employees of the selected construction companies, using disproportionate stratified sampling technique. The data collected were analyzed using Pearson product moment correlation. The questionnaire was validated using content validity. The reliability of the questionnaire was confirmed by determining the correlation coefficient of the data collected at two different periods. The study discovered informal groups has a significant effect on employee performance, there is a significant relationship between informal groups and their characteristics, there is a significant relationship between informal groups and self-confidence in Nigerian construction firms and Informal groups has significant influence on organizational performance in Nigeria